If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying x + 1 + x + 2 = 0 Reorder the terms: 1 + 2 + x + x = 0 Combine like terms: 1 + 2 = 3 3 + x + x = 0 Combine like terms: x + x = 2x 3 + 2x = 0 Solving 3 + 2x = 0 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-3' to each side of the equation. 3 + -3 + 2x = 0 + -3 Combine like terms: 3 + -3 = 0 0 + 2x = 0 + -3 2x = 0 + -3 Combine like terms: 0 + -3 = -3 2x = -3 Divide each side by '2'. x = -1.5 Simplifying x = -1.5
| 6(9)-2(9-5)=46 | | -2x+20=0 | | 83=q-17 | | 83=y-17 | | 2x+30=2x-35+x+15 | | y=5ln(x+3) | | -15=2t-21 | | 5X+4X+2+3X+10= | | 5(123.31)-20= | | 4y+9=13-2(y+3) | | 5(5)-4(5-3)=17 | | 2/3*n=24 | | n^(9/2)*n^(-5/2) | | 18+5w=8w | | 5(5)-4(-5-3)=17 | | 6x-18=7x+13 | | 15/2×1/3 | | 150x-3x^2=1000 | | x^2-21x+100=80 | | (4a^4)(b^4)(b^4)=(4ab)4 | | 24x+32x=32 | | 15/2×1/3×1/5 | | 11(11.21)-10= | | -9-b+b=-23 | | -8-12x=7-2x-6 | | 18a^3b^5+23b^2+5=0 | | 3(x-3/4)= | | .5x(5-7x)=8-(4x+6) | | 6p-5=7p+7-p | | h=-16t^2+100t+600 | | 15x^2-66x-45=0 | | 144+x^2=225 |